Promoting healthy trajectories for urban middle school youth through county‐funded, parks‐based after‐school programming. Issue 7 (29th April 2021) - Goodman, Allison C.; Ouellette, Rachel R.; D'Agostino, Emily M.; Hansen, Eric; Lee, Theodore; Frazier, Stacy L.
Abstract: Ongoing pressure for public schools to prioritize academics has increased attention on after‐school settings as a critical space for social‐emotional learning (SEL). After‐school programs are uniquely positioned to build protective and promotive factors that contribute to positive future orientation, especially within communities where systemic inequities create barriers to high school graduation, higher education, employment, and earnings. This study examines Fit2Lead Youth Enrichment and Sports (YES), a county‐funded, parks‐based after‐school collaboration for middle schoolers that merges mental health and recreation to promote healthy trajectories. Eight Miami neighborhood parks were selected based on county data indicating high rates of violence. An open trial design ( N  = 9 parks, 198 youth; ages 9–15; 40.5% female; 66.5% Black/African American, 24.9% Hispanic/Latinx, and 76.3% low‐income) tested hypotheses that participation for adolescents exposed to community violence would disrupt a commonly reported decline in self‐regulation and self‐efficacy, and mitigate risk for anxiety and depression. Youth completed questionnaires at the beginning and end of one school year. Paired t ‐tests revealed no changes from pre to post, and no differences by baseline levels of youth and parent mental health. Findings highlight the promise of prevention programs to disrupt downward trajectories for youth during the risky time of early adolescence.